A STUDY ON RELATIONSHIPS BETWEEN BATMAN AND HUSH IN BATMAN HUSH A PSYCHOLOGICAL APPROACH - I Made Bayu Kusumawardana (Lexicon, 2012)
This paper was intended to observe the relationships that developed between the two main characters in Batman Hush based on certain parameters. The parameters are character’s environment, social life and their choice to adapt to it. Through the process of analysis, the characters came into differentresult of relationship even though their conditions are quite similar.The mean used in this paper are Theory of Psychosocial Development. It’s a theory promoted by Professor Erik Erikson which separated human’s character development into 8 stages.